Dinamika Guru PAUD dalam Menjaga Martabat Profesi di Media Sosial - Nabila Asha Azzahra; Iftinan Iftinan; Fitra Faradila; Muhlisin Muhlisin; Abul Mafaakhir (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to analyze the digital behavior of Early Childhood Education (PAUD) teachers on social media and to formulate a Digital Role Model framework as an effort to protect children’s privacy in cyberspace. The study employs a qualitative approach using library research and content analysis. The findings reveal three typologies of ECE teachers’ digital behavior: documentation of learning, educational posts, and content exploitation. The findings indicate that the publication of children’s visual content without valid informed consent from parents has the potential to violate professional ethics for teachers and contravene Law No. 27 of 2022 on Personal Data Protection. The novelty of this study lies in the integrative formulation of the Digital Role Model, which positions the protection of children’s personal data as a central component of PAUD teachers’ professionalism in the digital age. This framework is built through three operational dimensions: the ability to self-filter posts, a commitment to protecting children’s identities, and the use of social media as a tool for professional academic reflection. Implementation of the model is recommended through the development of strict Standard Operating Procedures for the publication of children’s content within early childhood education settings